Peran Digital Marketing dalam Pengembangan Kegiatan Promosi UMKM Abon buana Desa Caruban Kecamatan Ringinarum - Ade Bagus Primadoni; Meilan Tri Wuryani; Rachmat Imam Muslim; Dian Kusumawati; Desi Fitriana Rahmawati (Hikamatzu | Journal of Multidisciplinary, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of regional economic development, including in Caruban Village, Ringinarum District. One growing MSME is Abon Buana, which faces challenges in expanding its product promotional reach to compete in an increasingly competitive market. Utilizing digital marketing is a strategic solution to increase promotional effectiveness while expanding its target market. This study aims to analyze the role of digital marketing in developing promotional activities for Abon Buana. The method used was descriptive qualitative through observation, interviews, and documentation. The results show that the implementation of digital marketing, particularly through social media (Instagram, Facebook, and WhatsApp Business) and marketplace platforms, contributes significantly to introducing products to the wider public, increasing interaction with consumers, and strengthening brand image. Creative content strategies tailored to local and global consumer trends have proven effective in attracting buyers. However, challenges include limited technology management capabilities, consistent content creation, and the need for ongoing mentoring. Thus, digital marketing plays a crucial role in strengthening the promotion of Abon Buana's MSMEs in Caruban Village, Ringinarum District, while also opening up opportunities to increase competitiveness in a broader market